The Development of Passing Variation Technique for Team Rajo Upat Teluk Singkawang - Ahmad Redo; Dian Estu Prasetyo; Maldin Ahmad Burhan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
The development of the world in the 21st century now has many people creating very sophisticated technologies, as well as in the world of sports. In everyday life, humans also need sports activities to keep their bodies healthy, fit and especially to avoid disease. The researcher uses the ADDIE model which consists of 5 stages, namely: analysis, design, development, implementation, and evaluation. In this study, researchers developed a product in the form of a variation of the Passing futsal exercise, the product produced was a book containing training materials in the futsal game, especially Based on the results in the development research as well as the trial phase that has been carried out by the researchers on the players of the Rajo Upat futsal team, Teluk Singkawang, on the variation of the Passing futsal exercise, the following data were obtained: The validity of the variation of the Passing futsal exercise was assessed by one validator, indicating that the development of the Passing futsal training model obtained an average percentage of 85.4% with a very valid category. The practicality of the variation of the Passing futsal exercise which was assessed from a questionnaire response of players who had been assessed by 1 coach with a percentage of 90% and 15 practitioners (Players of the Rajo Upat Futsal Team Teluk Singkawang) obtained an average percentage of 85% with a very practical category. The effectiveness of the variation of the Passing futsal exercise is obtained from the Passing test in the form of a trial of doing Passing that is reflected against the wall for 30 seconds which obtains a 75% percentage in the effective category. Based on some of the conclusions above, it can be concluded that this form of variation of the Passing futsal exercise meets the criteria of being very valid, very practical and very effective. This variation of the Passing futsal exercise is feasible to use in the training process